Une injonction d'individuation en actes - Cédric Frétigné (Les éditions de la Maison des sciences de l'Homme, 2004)
As a form of work-based learning, the placement in practice firms is meant to improve the employability of the unemployed and to facilitate their integration into the labour market. It is precisely in view of this professional (re) insertion that "counsellors" intervene and guide the trainees' job search. Based on a case study, this article describes the reactions of trainees to the counsellors' verdicts expressed in the diagnoses of their past professional experiences' their present experience of unemployment and their anticipated future.